Peramalan Prediksi Penjualan Garam Pada CV.Saltindo Megajaya Dengan Metode Least Square - Indah Sari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Along with the times at this time the development of information technology affects data to produce more accurate, fast and actual information to increase accuracy in decision making, including forecasting information systems in predicting salt sales that occur at CV.Saltindo Megajaya. With the information system, the forecasting process predicts salt sales can run effectively and efficiently and a decision is reached on the amount of salt that must be provided for the next month, so that there is no excess and shortage of salt stock in sales. Forecasting referred to in this study is forecasting with the least square method. Through the application of the least square method, researchers will carry out a prediction process using past data obtained by researchers from the company's leadership, Mr. Yulianto at the CV.Saltindo Megajaya agency.